ROLE OF BEDSIDE ULTRASOUND IN DETECTION OF BONE FRACTURES IN PEDIATRICS AND ADULTS - GoliKhatir, Iraj; Bozorgi, Farzad; Pashaei, Seyyedeh Masoume (Journal of Ayub Medical College Abbottabad, 2018)
During medical devices evolution many modalities and techniques like Computerized tomography, magnetic resonance imaging, wireless capsule endoscopy and double-balloon endoscopy were applied to provide enough evidences for final detection of diseases. As well as current procedures, sonography is a method that individuals are satisfied with it because of various conditions like non-invasive and cheap. Ultrasound is one of the procedures which can be used in diagnosis of fractures and has its own unique feature including different views at the same time with no radiation effects. It can show bones and plays an important role in initiation of disease, follow up of the patients. The aim of this investigation was to evaluate the Role of bedside ultrasound findings in patients with fractures. We concluded that ultrasound should be used as well as other methods to reach better outcomes. Keywords: Bedside ultrasound; Bone; Fractures; Paediatrics; Adults